2010
DOI: 10.1007/s11547-010-0534-z
|View full text |Cite
|
Sign up to set email alerts
|

Plantar fascia evaluation with a dedicated magnetic resonance scanner in weight-bearing position: our experience in patients with plantar fasciitis and in healthy volunteers

Abstract: Imaging the ankle/hind foot in the upright weight-bearing position with a dedicated MR scanner and a dedicated coil might enable the identification of partial tears of the plantar fascia, which could be overlooked in the supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…A study comparing patients with clinically diagnosed plantar fasciitis and healthy volunteers in a dedicated MR scanner showed that 25% of the patients with clinical suspicion of plantar fasciitis had normal MRI scans. 9 Hall et al demonstrated that 36% of the patients in their study had no pathology on MRI scan to explain the cause of heel pain. 33 In another study, MRI scans did not confirm clinical diagnosis of plantar fasciitis in 24% of the cases.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A study comparing patients with clinically diagnosed plantar fasciitis and healthy volunteers in a dedicated MR scanner showed that 25% of the patients with clinical suspicion of plantar fasciitis had normal MRI scans. 9 Hall et al demonstrated that 36% of the patients in their study had no pathology on MRI scan to explain the cause of heel pain. 33 In another study, MRI scans did not confirm clinical diagnosis of plantar fasciitis in 24% of the cases.…”
Section: Discussionmentioning
confidence: 88%
“…3 Plantar fasciitis is generally a self-limiting condition but recovery can take several months. 4,5 Approximately 10% to 20% of patients develop persistent and often disabling symptoms 6-10 that can have a significant effect on mobility, day-to-day activities, work, and general well-being. Diagnosis is mainly based on clinical assessment; however, recently there has been a surge in investigating these cases with magnetic resonance imaging (MRI) scans as it provides excellent soft tissue as well bony resolution and hence is recommended as an appropriate imaging choice.…”
mentioning
confidence: 99%
“…Meta-analysis of the two studies that measured proximal plantar fascia thickness included a total of 165 PHP participants and 174 control participants [ 45 , 49 ]. PHP participants had a mean plantar fascia thickness that was 3.17 mm (95% CI 1.95 to 4.39) thicker than control participants ( p < 0.001) – see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One MRI study reported the number of people with plantar fascia thickness > 4 mm [ 49 ]; this study found 15 (75%) of the PHP participants and none (0%) of the control participants presented with this finding.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various diseases related to this symptom, such as Achilles tendinopathy, tarsal tunnel syndrome and plantar fascia ruptures, the most common is plantar fasciitis (1,2) . Plantar fasciitis is defined as an inflammatory and degenerative disorder located in the proximal region of the central band of the plantar fascia (1,3,4) . Studies deduce that it affects approximately one million Americans every year, accounting for 1% of all orthopedic appointments in the United States (US), at an annual cost of 192 to 376 million dollars (2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%